Contact calls of the northern and southern white rhinoceros allow for individual and species identification - Cinková, Ivana; Policht, Richard (PloS one, 2014)
Inter-individual relationships particularly in socially living mammals often require a well-developed communication system. Vocal and olfactory signals are the most important for the communication of rhinos, however, their vocal communication has been investigated to a very limited extent so far. White rhinos have the most developed social system out of all the rhinoceros species and vocal signals might therefore play an important role in their social interactions. We recorded repetitive contact pant calls from six captive northern white rhinos (Ceratotherium cottoni) and 14 captive and free-ranging southern white rhinos (Ceratotherium simum) and examined if they transmit information about individual identity, species, social context and age class. Discriminant analyses revealed that a high percentage of the pant calls of both species could be classified to a correct individual. We calculated signature information capacity of pant calls recorded from adult animals in isolation at 3.19 bits for the northern white rhinos and at 3.15 bits for the southern white rhinos, which can potentially allow for a vocal discrimination of nine individuals of both species. We found that pant calls varied by species. Northern white rhinos had longer calls and also differed from the southern white rhinos in several frequency parameters of their calls. We also analysed the pant calls of southern white rhinos for the differences between the age classes and between social contexts in which they were recorded. Our results show that pant calls carry information about individual, species, age class and context. The ability to recognize this information would allow rhinos, in addition to olfactory cues, to communicate with highly increased accuracy. A better understanding of communication of white rhinos has potential practical use in their management and conservation particularly because of the low breeding success of white rhinos in captivity.
Keywords: komunikace zvířat; vokalizace zvířat; Animal Communication; mužské pohlaví; ženské pohlaví; druhová specificita; zvířata; Female; Vocalization, Animal; Perissodactyla; Male; Species Specificity; Animals